2004
DOI: 10.1002/jcop.20007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ecological risk and perceived discrimination on the psychological adjustment of African American and European American youth

Abstract: ⅢThe purpose of the present study was to examine the role of cumulative ecological risk (i.e., neighborhood Youth exposed to psychosocial stressors such as poverty, chronic neighborhood disadvantage, violence, and stressful life events are at heightened risk for the development of a number of severe problems, including externalizing disorders~Attar, Guerra,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(116 citation statements)
references
References 46 publications
10
106
0
Order By: Relevance
“…Williams and Williams-Morris (2000) suggested that discrimination may assault victims' ego identity and contribute to the internalization of negative stereotypes. Discrimination may also threaten one's sense of control and foster hopelessness (Perlow, Danoff-Burg, Swenson, & Pulgiano, 2004). These factors in turn may lead to depression, anxiety and other mental disorders (Williams & Williams-Morris, 2000).…”
Section: Discrimination and Mental Healthmentioning
confidence: 99%
“…Williams and Williams-Morris (2000) suggested that discrimination may assault victims' ego identity and contribute to the internalization of negative stereotypes. Discrimination may also threaten one's sense of control and foster hopelessness (Perlow, Danoff-Burg, Swenson, & Pulgiano, 2004). These factors in turn may lead to depression, anxiety and other mental disorders (Williams & Williams-Morris, 2000).…”
Section: Discrimination and Mental Healthmentioning
confidence: 99%
“…Both observational and selfreport data suggest that experiencing racial discrimination is not uncommon for a majority of African American adolescents (Fisher, Wallace, & Fenton, 2000;Gregory, 1995;Sellers, Copeland-Linder, Martin, & Lewis, 2006). A growing body of research indicates that these experiences with racial discrimination are associated with a number of deleterious psychological, educational, and social outcomes for African American adolescents (e.g., Clark, Coleman, & Novak, 2004;Neblett, Philip, Cogburn, & Sellers, 2006;Prelow, Danoff-Burg, Swenson, & Pulgiano, 2004;Sellers et al, 2006;Simons et al, 2002;Wong, Eccles, & Sameroff, 2003). As a result, experiencing racial discrimination constitutes a significant risk to the healthy development of African American youth (Cunningham, Swanson, Spencer, & Dupree, 2003;Spencer, Dupree, & Hartmann, 1997).…”
mentioning
confidence: 99%
“…For example, significant literature has demonstrated the negative effects of racism or discrimination on mental health outcomes among African American, Latino, Asian American, and Native American youth and adults (Rosenbloom and Way 2004;Whitbeck et al 2002;Wong et al 2003). Studies indicate that the negative effects of discrimination on youth developmental outcomes include increased delinquency and problem behaviors such as shoplifting, skipping class, lying to parents, cheating, stealing cars, and bringing drugs or alcohol to school (Okamoto et al 2009;Prelow et al 2004;Wong et al 2003) as well as internalizing problems such as depressive symptoms (Seaton et al 2008) and anxiety (Gaylord-Harden and Cunningham 2009;Hwang and Goto 2008). Similarly, studies on Latino and Asian American immigrant youth suggest that acculturative stress is a significant predictor of poor mental health-including internalizing problems (e.g., withdrawal, anxiety, somatic and depressive symptoms), and externalizing behavior problems (i.e., delinquency, aggressive behaviors) (Dinh et al 2008;Gil et al 2000;Hovey and Magaña 2002;Vega and Gil 1998).…”
Section: Psychological Trauma Causesmentioning
confidence: 99%